FACTORS AFFECTING THE FORMATION OF THE STRATEGY OF THE COMMERCIAL ACTIVITY OF THE ENTERPRISE (Marketing Journal, 2026)
This article examines the factors influencing the development of a commercial strategy for a retail enterprise and the methods for analyzing the environment in which the enterprise operates. A SWOT analysis is conducted, and the competitiveness of a specif ic retail enterprise is assessed.
Keywords: commercial activity strategy; factors shaping strategy; long -term objectives; competitiveness factors; competitiveness assessment